2020
DOI: 10.1371/journal.pone.0230835
|View full text |Cite
|
Sign up to set email alerts
|

Role of syndecan-1 in the interaction between dendritic cells and T cells

Abstract: Syndecan-1 (Sdc-1) is a heparan sulfate proteoglycan that can bind cytokines and chemokines via its heparan sulfate side chains, and has immunomodulatory properties in experimental models. Sdc-1 expression has been reported on dendritic cells (DC) and T cells. The potential role of Sdc-1 in DC-T cell interaction has not been investigated yet. We postulate that Sdc-1 is involved in DC-T cell interaction and may influence graft survival in an allogeneic transplant model. Sdc-1 expression on bone marrow-derived D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…As expected, most of the CD138 + cells isolated by MACS were myeloma cells mixed with a few normal immunocytes, including T cells and monocytes (Figures S2‐6). Notably, the SDC1/CD138 gene product was identified as a weakly expressed in T cells in our study, which was consistent with previous findings that its expression was described in dendritic cells, activated T cells and macrophages 26–29 …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, most of the CD138 + cells isolated by MACS were myeloma cells mixed with a few normal immunocytes, including T cells and monocytes (Figures S2‐6). Notably, the SDC1/CD138 gene product was identified as a weakly expressed in T cells in our study, which was consistent with previous findings that its expression was described in dendritic cells, activated T cells and macrophages 26–29 …”
Section: Resultssupporting
confidence: 93%
“…Notably, the SDC1/CD138 gene product was identified as a weakly expressed in T cells in our study, which was consistent with previous findings that its expression was described in dendritic cells, activated T cells and macrophages. [26][27][28][29] As MM is a plasma cell neoplasm, myeloma cells undergo the same V(D)J recombination process and somatic hypermutation as B cells and often exhibit singlecell clonal amplification. 30 Next, we checked the malignant cell clonotypes through single-cell V(D)J sequencing data.…”
Section: Identification Of Malignant Cells and Clonotypes In MM At Si...mentioning
confidence: 99%
“…Glypican 5 appears in DCs at all stages, but not monocytes or macrophages, while glypican-1 was absent only from monocytes [182]. A number of other studies confirmed the presence of all four syndecans on DCs by flow cytometry [183][184][185]. This expression data raises the possibility that at least in the context of monocytes, macrophages and DCs there are likely to be multiple GAGbearing molecules on the cell surface, conceivably bearing GAG chains with distinct, core protein-specified properties.…”
Section: Heparan Sulfate Proteoglycans and Leucocytesmentioning
confidence: 67%
“…Leucocyte representations were generated with the aid of www.biorender.com. For references see [177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193].…”
Section: Heparan Sulfate Proteoglycans and Angiogenesismentioning
confidence: 99%
“…SDC-1 has immunomodulatory capabilities and is essential in controlling lung inflammation [ 37 , 38 ]. The respiratory mucosa, including plasma cells, tissue-resident memory B cells, and plasmablasts, secretes the antibody IgA [ 39 ].…”
Section: Resultsmentioning
confidence: 99%